The Electromechanical Impedance Method and its Application for Paint Coating Damage Detection - Liu, Xianhua; Paurobally, R. (Springer-Verlag, 2011)
This paper reports research findings of a corrosion sensing project for applying the electromechanical impedance method for paint coating damage detection. A piezoceramic patch attached to a structure can excite micro and local structural vibration when an alternating or random low voltage signal is applied. The resistance of the structure to the vibration excitation can be measured in terms of the electromechanical impedance. When a structure is damaged the impedance will change. This has been used for structural damage detection. The application of the impedance method for paint coating damage detection is a new exploration. In this paper, the impedance method is first introduced and then research findings on the feasibility of paint coating damage detection by the method is both theoretically and experimentally studied and results discussed.